2017
DOI: 10.1101/165043
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The largest SWI/SNF polyglutamine domain is a pH sensor

Abstract: Polyglutamines are known to form aggregates in pathogenic contexts, such as Huntington disease. However, little is known about their normal biological role. We found that the polyglutamine domain of the Snf5 subunit of yeast SWI/SNF complex is required for efficient induction of glucose-repressed genes. Both transient cytosolic acidification and histidines within the polyglutamine domain were required for efficient transcriptional reprogramming. We hypothesized that a pHdependent oligomerization could be impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…A similar process was also recently reported for another important stress-associated transcription factor in yeast (74). Snf5, a component of the SWI/SNF complex responsible for the expression of many glucose-repressed genes, has a poly-Q stretch that the authors find is crucial for transcriptional activation.…”
Section: Jbc Reviews: Sensing By Phase Separationsupporting
confidence: 77%
“…A similar process was also recently reported for another important stress-associated transcription factor in yeast (74). Snf5, a component of the SWI/SNF complex responsible for the expression of many glucose-repressed genes, has a poly-Q stretch that the authors find is crucial for transcriptional activation.…”
Section: Jbc Reviews: Sensing By Phase Separationsupporting
confidence: 77%
“…For example, several proteins associated with transcription and chromatin remodeling contain low complexity regions. One protein, Snf5p, is glutamine and asparagine rich and also appears to phase separate in response to pH stress (Gutierrez, Brittingham, Wang, Fenyo, & Holt, ). It is intriguing to speculate that inherent sensing abilities via low complexity regions could provide a wide array of proteins, particularly those involved in global functions such as transcription and translation, with a rapid mechanism for responding to transient stress.…”
Section: Sup35p and Phase Separationmentioning
confidence: 99%
“…Early work in Drosophila melanogaster produced mixed results: one study indicated that acidification had little impact on the production of heat shock proteins ( Drummond et al, 1986 ), while later work showed that Hsf1 trimerization, a key activation step, could be induced by acidification in vitro ( Zhong et al, 1999 ). More recently, acidification during stress has been shown to influence cell signaling ( Dechant et al, 2010 ; Gutierrez et al, 2017 ) and appears to be cytoprotective ( Munder et al, 2016 ; Joyner et al, 2016 ; Coote et al, 1991 ; Panaretou and Piper, 1990 ). The extent to which this adaptive effect of pH depends on the core transcriptional stress response remains unknown.…”
Section: Introductionmentioning
confidence: 99%